2014-2015 Global food policy report - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
This 2014–2015 Global Food Policy Report is the fourth in an annual series that provides a comprehensive overview of major food policy developments and events. In this report, distinguished researchers, policymakers, and practitioners review what happened in food policy in 2014 at the global, regional, and national levels, and—supported by the latest knowledge and research—explain why. This year’s report is the first to also look forward a year, offering analysis of the potential opportunities and challenges that we will face in achieving food and nutrition security in 2015. The year 2014 was marked by advances and setbacks in agriculture, food security, and nutrition. The Millennium Development Goal of halving poverty by 2015 was achieved. World food prices fell to their lowest level since 2010. Nutrition remained prominent: the Second International Conference on Nutrition in Rome proposed actions to end malnutrition, membership in the Scaling Up Nutrition (SUN) movement expanded, and new research highlighted the importance of factors such as water and sanitation and the role of women in battling malnutrition. Debate began on the draft post-2015 Sustainable Development Goals, sharpening the world’s focus on the building blocks of food and nutrition security. Significant commitments to combating climate change were made, particularly by China and the United States. Middle income countries, home to the majority of the world’s hungry and malnourished people, continued their efforts to improve food security and nutrition at home, with Brazil and China, for example, expanding investments in agriculture and knowledge and technology transfers with the global South